2016
DOI: 10.20471/acc.2016.55.03.17
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sleep Deprivation on the Brain

Abstract: SUMMARY -Each sleep phase is characterized by specifi c chemical, cellular and anatomic events of vital importance for normal neural functioning. Diff erent forms of sleep deprivation may lead to a decline of cognitive functions in individuals. Studies in this fi eld make a distinction between total sleep deprivation, chronic sleep restriction, and the situation of sleep disruption. Investigations covering the acute eff ects of sleep deprivation on the brain show that the discovered behavioral defi cits in mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The high prevalence of SD among nurses is due to work shifts and it seems that globally there is a lack of a system of proper shift distribution to ensure nurses a smooth circadian rhythm and avoid additional mental and physical strain resulting from poor sleep quality (Slavish et al, 2020). SD has been associated with more medication errors, lower work performance, physical and emotional strain, and increased family problems (Trošt Bobić et al, 2016; Zeng et al, 2022). Nurses who work in shifts tend to have more need for sleep (Korompeli et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high prevalence of SD among nurses is due to work shifts and it seems that globally there is a lack of a system of proper shift distribution to ensure nurses a smooth circadian rhythm and avoid additional mental and physical strain resulting from poor sleep quality (Slavish et al, 2020). SD has been associated with more medication errors, lower work performance, physical and emotional strain, and increased family problems (Trošt Bobić et al, 2016; Zeng et al, 2022). Nurses who work in shifts tend to have more need for sleep (Korompeli et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that shift work is associated with a greater risk for disorders affecting physical, mental, and emotional health of individuals (Park, Park, Bae, & Kang, 2023; Torquati, Mielke, Brown, Burton, & Kolbe-Alexander, 2019). Shift work can have significant negative impact in circadian rhythm (Booker, Magee, Rajaratnam, Sletten, & Howard, 2018; Touitou, Reinberg, & Touitou, 2017) and metabolism (Ljevak et al, 2022), although it has been associated with hypertension, breast cancer, and impaired social and family life (Trošt Bobić et al, 2016; Zeng et al, 2022). Studies have shown a decline in social parameters for nurses, as SD causes reduced endurance to maintain usual daily activities, although prolonged exposure to shift work may affect cognitive dysfunction and increase the risk of errors, or even injury, especially during night shift (Sarafis et al, 2016).…”
mentioning
confidence: 99%
“…, insomnia, obstructive sleep apnea, and neurodegenerative disorders) can disrupt sleep ( Ogilvie & Patel, 2017 ). Lack of sleep can influence glucose tolerance ( Chaput et al, 2007 ), insulin sensitivity ( Nedeltcheva, Imperial & Penev, 2012 ), formation of atherosclerotic plaques ( Cherubini et al, 2021 ), oxidative stress ( Xue et al, 2019 ), and the autonomic regulation of the brain ( Bobić et al, 2016 ). These factors can lead to an increased risk of cardiovascular disorders such as coronary artery disease ( Aggarwal et al, 2013 ), obesity ( Liu et al, 2013 ), arrhythmias, diabetes mellitus ( Spiegel, Leproult & Van Cauter, 1999 ), and hypertension ( Fang et al, 2012 ; Gottlieb et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%